LITERACY PRACTICE: READING COMMUNITY AND ITS CONTRIBUTION TO SELF-READING - Aulia Nisa' Khusnia (Journal of English Language Teaching and English Linguistics, 2020)
The reading community is the local group of Indonesian in urban area bear on reading. The member provides an opportunity for members to support literacy during the community day and extend reading out of the community day. The reading community activities are individual and grouping reading practice. Besides, the members’ background is in different age and study background. The present study designed to explain the reading members’ on reading motivation, problem and strategy. Furthermore, the researcher explained more about the literacy practice, such as self-reading to depict the reading activity of the member, in terms of time and frequency. The researcher used a mixed method. It is integrating between quantity and qualitative data. Observation applied to get a further background of the members’  reading motivation, problem as well as strategy. Besides, the one on one interview used for describing the self-reading. The respondents of the research are 20 members in a group of the reading community. The members were selected randomly.  The result showed members’ reading motivation, reading problem and reading strategy. Those covers curiosity, aesthetic involvement, challenge, recognition, and grade. A reading problem consists of low memory to remember, progressive decline in visual sensitivity, a result of the normal process affect reading, poor reading skill and feel out of place in the conversation that moves quickly.  Reading strategy such as using prior knowledge/previewing, predicting, identifying the main idea and summarization, questioning, making inferences, visualizing as well as their self-reading in terms of time and frequency.